Tata Kelola Zakat dan Kepercayaan Institusional:Studi Persepsi Muzakki (ASN) terhadap BAZNAS Provinsi Banten - Heri Sapari Kahpi; Amiruddin, Suwaib (Suwaib Amiruddin Foundation, 2025)
The success of zakat institutions in modern Muslim society is strongly influenced by the quality of governance and the level of trust among Muzakki (zakat payers). This study aims to examine the relationship between zakat governance and institutional trust, focusing on public perceptions of BAZNAS (Badan Amil Zakat Nasional) as the official zakat management body in Indonesia. Using a quantitative approach with 90 respondents from the State Civil Apparatus (ASN), the research applies Structural Equation Modeling (SEM) to analyze the effects of governance dimensions—transparency, accountability, participation, and efficiency—on institutional trust. The findings indicate that zakat governance has a positive and significant impact on public trust, with transparency and accountability emerging as dominant factors. These results contribute significantly to strengthening the legitimacy and effectiveness of formal zakat institutions in Indonesia. Theoretically, this study enriches the literature on zakat governance by offering an integrative model that links public perceptions with institutional trust